Quantum subgroups of simple twisted quantum groups at roots of one - García, Gastón Andrés (2018)
Let G be a connected, simply connected simple complex algebraic group and let ∈ be a primitive ℓth root of unity with ℓ odd and coprime with 3 if G is of type G₂. We determine all Hopf algebra quotients of the twisted multiparameter quantum function algebra Oφ∈ (G) introduced by Costantini and Varagnolo. This extends the results of Andruskiewitsch and the first author, where the untwisted case is treated.